Impact of Blood Type on Treatment Response and Survival in HER2-Negative Metastatic Gastric Cancer - Yıldırım, Sedat; Alan, Özkan; Türkoğlu, Ezgi; Sariyar Busery, Nisanur; Doğan, Akif; Akdağ, Goncagül; Şahika Yıldız, Hacer; Topal, Alper; Sakin, Abdullah; Başoğlu, Tuğba; Ay Ersoy, Seval; Odabaş, Hatice; et al. (Cerrahpaşa Medical Journal, 2025)
Objective: Metastatic gastric cancer is one of the most lethal malignancies. Recent studies indicate that the O blood group has better survival than the non-O blood group. In this study, the aim was to evaluate the impact of blood group O and non-O blood groups on survival outcomes and treatment responses in gastric cancer patients. Methods: Between January 2012 and June 2024, 187 patients with metastatic gastric cancer treated at Kartal Dr. Lütfi Kırdar City Hospital were retrospectively analyzed. Patients were divided into 2 groups: O blood group (n = 82) and non-O blood group (n = 105). The prognostic role of blood groups and their impact on survival outcomes was investigated. Results: Median overall survival was 15.7 months in the O blood group and 12.9 months in the non-O blood group (P = .04). There was no significant difference between the groups in terms of progression-free survival (7.9 months versus 7.0 months, P = .11). Disease control rates were 69.5% in the O Rh +/− group and 63.3% in the other groups. In subgroup analyses, a borderline significant interaction (P = .08) was observed between the blood group and Eastern Cooperative Oncology Group (ECOG) PS (Performance Status). In multivariate analysis, ECOG performance score was found to be an independent prognostic factor (hazard ratio = 1.6, P = .003), whereas blood group was not found to be an independent prognostic factor (P = .16). Conclusion: The study found thatpatients with bloodgroup O exhibited better survival rates inmetastatic gastric cancer; however, the blood group was not identified as an independent predictor of survival. The primary determinant of survival outcomes remained the patient’s performance status. Therefore, while bloodgroup may serveas an additionalprognostic indicator, its utility requires further validation throughlarger scale studies. Cite this article as: Yildirim S, Alan Ö, Turkoglu E, et al. Impact of blood type on treatment response and survival in HER2-negative metastatic gastric cancer. Cerrahpaşa Med J 2025, 49, 0042, doi: 10.5152/cjm.2025.25042.